Identification of shared mechanisms between Alzheimer's disease and atherosclerosis by integrated bioinformatics analysis - Jukun Wang; Jing Yao; Zhe Wang (European Journal of Medical Research)
Abstract Alzheimer's disease (AD) and atherosclerosis (AS) are two interacting diseases mostly affecting aged adults. AD is characterized by the deposition of neuritic plaques mainly consisting of Aβ, and AS is defined by the formation of atheromatous plaque along the vascular wall. The shared mechanisms underlying the pathogenesis of AD and AS remain unclear. Here we applied several bioinformatic analyses of bulk sequencing data sets of AD brain tissues and atherosclerotic plaques to seek relevant genes between AD and AS. WIPF3, was identified as the most affected gene in both diseases using weighted gene co-expression network analysis, machine-learning-based Lasso Cox regression analysis and random forest analysis. Furthermore, immune cell infiltration analysis of AS data sets and cell portion of single-cell RNA sequencing data from AD patients revealed an essential role of inflammation in the co-occurrence of AD and AS. Taken together, WIPF3 deficiency and inflammation may simultaneously mediate both AD and AS and could be potential targets for the prevention and therapy of these two closely related diseases.